EFEKTIVITAS ORGANISASI KOPERASI PENGEMUDI TAKSI (KOPSI) DALAM MEMBERIKAN PELAYANAN JASA ANGKUTAN di KOTA PEKANBARU - Putri, Riska Apriani; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The result of this research indicates that there are some problems in Kopsi’s services to consumer. In the indicator of implementation of input Kopsi Organization, there are weaknesses in coaching the new members. It makes the services that are given by Kopsi to consumer is deficient. The process of implementation of Kopsi programs that have been planned, it needs the improvement. The improvement is in the process of socializing about Kopsi to society. Through the good socialization, it will give good understanding about the existence of Kopsi in Pekanbaru. The output of organization has been achieved well because the consumer of Kopsi Transport Service still in the stable category and the outcome is in the stable category also. The good output will produce the good outcome also. Seeing the progress that happen in society.Keywords : Effectiveness, Organization Kopsi, Service